The Influence of Universal Design for Learning (UDL) on the Learning Outcomes of IPAS Students in Inclusive Classes - Tantika, Yevi Sylvia; Arbarini, Mintarsih; Suminar, Tri (UIN Sultan Aji Muhammad Idris Samarinda, 2025)
Education is a basic right for all students, including students with special needs (PDBK). Universal Design for Learning (UDL) is a learning design that can design learning so that learning can be felt by all students. In this study, the method used was an experimental method with a control group and an experimental group. Where the experimental group received learning using UDL while the control group used conventional methods. Three-factor analysis of variance with repeated measurements was used to evaluate the differences between pretest and posttest in developing lesson plans that were accessible to all students. The results showed that the implementation of UDL significantly improved learning outcomes for students in inclusive classes. In conclusion, the implementation of UDL can improve learning outcomes for students in inclusive classes, although further training is needed for teachers to optimize the implementation of UDL and cooperation from various parties is needed to be able to create an appropriate educational climate for students with special needs.